Reflective Crack Mitigation Using AST Interlayer over Soil-Cement Base for Flexible Pavements - Bhuyan, Mohammad Reza-Ul-Karim; Khattak, Mohammad Jamal (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
Flexible pavement over soil-cement base deteriorates over time due to reflective cracking caused by the shrinkage of such base. The propagation of the reflective cracks in overlaying hot mix asphalt (HMA) could be mitigated by installing interlayer system. State of Louisiana, USA has been utilizing Asphaltic Surface Treatment (AST) as an interlayer between the soil-cement base and HMA to mitigate reflective cracking. To evaluate the field performance of AST interlayer, flexible pavement projects with and without AST interlayer over soil-cement bases were compared in this study. From the Pavement Management System (PMS) database of Louisiana, 27 AST interlayer projects (70 miles) and 46 No AST interlayer projects (175 miles) were selected for comparison. The service lives of these projects were assessed using the time series cracking, rutting, and international roughness index (IRI) data. It was found that the projects with AST interlayer produced on average 14.3 and 14.7 years of service lives for transverse and alligator cracking, respectively. On the other hand, the average service lives of No AST interlayer projects were 11.6 and 12.5 years for such cracks, respectively. Hence, the AST interlayer projects gained 2.7 and 2.2 years of service life for transverse and alligator cracking, respectively. However, the service life based on rut data showed a loss of 3.2 years for AST interlayer projects (16.2 years). Furthermore, the longitudinal cracking and IRI exhibited no improvements. In summary, AST interlayer can mitigate transverse and alligator cracking but slightly increase the rutting potential of the pavement.